Tinjauan Hukum Islam Terhadap Praktik Tanam Bulu Mata (Eyelash Extension) di Kecamatan Nipah Panjang - Mida Ennike Saputri; Haeran Haeran; Siti Fatimah; Kurniawan Kurniawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine the practice of eyelash extensions in Nipah Panjang District and the Islamic legal review of the practice of eyelash extensions in Nipah Panjang District. This type of research is qualitative research with an empirical and normative juridical approach. Data sources are in the form of primary data sources and secondary data sources. Data collection procedures through observation, interviews and documentation. Data analysis techniques through editing, reconstruction and data systematics. The conclusions obtained are: first, the practice of eyelash extensions in Nipah Panjang District is widely favored by the community, especially teenagers who want to follow the trend. Second, the Islamic legal review of the practice of eyelash implantation in Nipah Panjang District is not in accordance with Islamic law which means changing the creation of Allah SWT such as by connecting false hair which is prohibited by Allah SWT, this eyelash extensions also has a greater negative impact by hurting the eyes. Acts that hurt oneself are prohibited by Allah SWT, and eyelash extensions cause more harm than benefits.